2015
DOI: 10.1002/ehf2.12075
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a pilot randomized controlled trial to assess the role of intravenous ferric carboxymaltose in Asian patients with heart failure (PRACTICE‐ASIA‐HF)

Abstract: AimsIron deficiency (ID) is highly prevalent in patients with heart failure (HF) worldwide regardless of haemoglobin levels. Results from therapeutic trials of intermittently dosed intravenous (i.v.) iron are promising in the ambulatory Caucasian population with HF with reduced left ventricular ejection fraction, although evidence is scarce in Asia. The Pilot Randomized Controlled Trial to Assess the Role of Intravenous Ferric Carboxymaltose in Asian Patients with Heart Failure aims to assess the effect of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The study design has been published. 15 The study protocol was approved by the local ethics institutional regulatory board and conducted in accordance with the principles of the World Medical Association Declaration of Helsinki on ethics in medical research and International Conference on Harmonization guidelines for Good Clinical Practice. Written informed consent was obtained from all participants.…”
Section: Study Design and Oversightmentioning
confidence: 99%
“…The study design has been published. 15 The study protocol was approved by the local ethics institutional regulatory board and conducted in accordance with the principles of the World Medical Association Declaration of Helsinki on ethics in medical research and International Conference on Harmonization guidelines for Good Clinical Practice. Written informed consent was obtained from all participants.…”
Section: Study Design and Oversightmentioning
confidence: 99%
“…Iron plays a key role in oxygen uptake, transport, and storage, as well as oxidative metabolism in the skeletal muscle; it is also involved in erythropoiesis.13,14 However, erythropoiesis remains undisturbed until late in the course of iron depletion.15,16 Indeed, it has been reported that iron deficiency (ID) with or without anemia impairs the aerobic performance and leads to fatigue and exercise intolerance. [17][18][19] It is also known that the intravenous repletion -as opposed to oral administration -20 of iron in patients with HFrEF improves functional capacity, symptoms and QoL and may be associated with reduced hospitalization rates for worsening in HF. 10,21 ID is an extremely common nutritional disorder that affects up to 2 billion people worldwide,15 and it has recently been reported as a frequent co-morbidity in stable HF patients 22-24.…”
mentioning
confidence: 99%
“…Very recent data have shown that patients with HF who are iron deficient are unlikely to benefit from oral iron administration, because data from the IRONOUT HF study have shown that oral iron is poorly absorbed in the duodenum and its prescription not associated with an increase in the patients' peak VO 2 value . However, further studies are well under way to strengthen our views and positive evaluations of treating iron deficiency in patients with HF, for example, the PRACTICE‐ASIA‐HF study, the FAIR‐HF 2 trial, or the FAIR‐HFpEF trial …”
mentioning
confidence: 99%